PERAN PENYULUH PERTANIAN DALAM MENGGUNAKAN ALAT BANTU PENYULUHAN PADA KEGIATAN BUDIDAYA PADI SEHAT DI KELOMPOK TANI “PERDI I” DESA DILEM KECAMATAN KEPANJEN KABUPATEN MALANG - Mera, Meriana Dappa; Mutiara, Farah; Suwasono, Son (Universitas Tribhuwana Tunggadewi, 2019)
The purpose of this study was to determine the role of field agricultural instructors in the use of extension equipment in healthy rice cultivation activities and to analyze the factors associated with the use of extension equipment in the